CHALLENGES OF UNEMPLOYMENT IN INDONESIA: TRENDS, ISSUES AND POLICIES - Laila Nagib; NFN Ngadi (Jurnal Kependudukan Indonesia, 2008)
A rapid decline oflndonesia 's economy during the crisis of 1997-1998, has widely affected the quality of people life, including the declining labour demand, massive lay-offs, and shrinking formal employment. This situation will continue confirming Indonesia as a labour surplus country, due to limited productive working opportunities can be created by slower economic growth against the growing of new entrance in the labour market. This paper which is based on the secondary data mainly SAKERNAS data (1996-2004) from BPS Statistics Indonesia, describes issues and challenges of unemployment in Indonesia, with focus on the illustration of the unemployment trends, some issues on unemployment and related aspects, and how the development policies address the challenges of unemployment. The official open unemployment rate has been slowly increasing, even during the economic boom ( 1995-1996), and continues rising up to about I 0% in 2004. The incidence of open unemployment has been more pronounced among women, more educated, and in the urban areas. Other issues concerning unemployment deal with particularly vulnerable groups such as women, youth and migrant workers. Underemployment is more serious concern which is indicated as underutilizing people's potential, and the main factor of working poor. Almost half of Indonesia's labour force has involved in low productive works, either with low work hours or low income. Indonesia has faced big challenges to find way out in reducing the unemployment rate as well as poverty. The employment policy should focus on creating more full productive jobs and priorities the policy and protection for the more vulnerable groups.Keywords: unemployment, underemployment, vulnerable groups, employment policy